2023
DOI: 10.3389/fendo.2023.1149239
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role and mechanism of insulin resistance in metabolic disease

Abstract: Insulin resistance (IR) plays a crucial role in the development and progression of metabolism-related diseases such as diabetes, hypertension, tumors, and nonalcoholic fatty liver disease, and provides the basis for a common understanding of these chronic diseases. In this study, we provide a systematic review of the causes, mechanisms, and treatments of IR. The pathogenesis of IR depends on genetics, obesity, age, disease, and drug effects. Mechanistically, any factor leading to abnormalities in the insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 318 publications
2
48
0
Order By: Relevance
“…Given that there is a linking mechanism between obesity, inflammation, and IR, the predominance of the type 1 inflammatory response in AT may be involved in the etiopathogenesis of altered insulin signaling. In contrast to AT type 1 inflammation in obesity, type 2 inflammatory conditions are a part of AT immune homeostasis regulation in lean healthy individuals [111,159]. It has been suggested that the initiation of generalized low-grade inflammation in obesity may be triggered by the production of chemokines by adipose cells, the release of damage-associated molecular patterns (DAMPs) from necrotic AT, augmented rates of lipolysis with a subsequent increase in the flux of nonesterified fatty acids, and hypoxia with activation of hypoxia-induced factor (HIF)-1, which controls the expression of proinflammatory proteins [160].…”
Section: Inflammatory Response and Ir (See Also The Summary In Figure...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that there is a linking mechanism between obesity, inflammation, and IR, the predominance of the type 1 inflammatory response in AT may be involved in the etiopathogenesis of altered insulin signaling. In contrast to AT type 1 inflammation in obesity, type 2 inflammatory conditions are a part of AT immune homeostasis regulation in lean healthy individuals [111,159]. It has been suggested that the initiation of generalized low-grade inflammation in obesity may be triggered by the production of chemokines by adipose cells, the release of damage-associated molecular patterns (DAMPs) from necrotic AT, augmented rates of lipolysis with a subsequent increase in the flux of nonesterified fatty acids, and hypoxia with activation of hypoxia-induced factor (HIF)-1, which controls the expression of proinflammatory proteins [160].…”
Section: Inflammatory Response and Ir (See Also The Summary In Figure...mentioning
confidence: 99%
“…Apart from the dominant result of IR, which is T2DM, the metabolic consequences of IR include a broad spectrum of diseases and pathologic conditions, such as hypertension, dyslipidemia, visceral adiposity, nonalcoholic fatty liver disease (NAFLD), ovarian dysfunction and hyperandrogenism in women, acromegaloid features, hyperuricemia, elevated inflammatory markers, endothelial dysfunction, a prothrombic state, cancer, and neurodegenerative disorders, including AD [107][108][109][110]. Consequently, IR is a permanent component of metabolic syndrome, a cluster of conditions that occur together, increasing the risk of heart disease, stroke and T2DM [111]. In addition, an early and common manifestation of severe IR is skin changes known as acanthosis nigricans that usually develop in skin folds, such as the back of the neck, axilla and groin, and involve darkening and thickening of the skin (velvety overgrowth of the epidermis) [108].…”
Section: Insulin Resistance (Ir)mentioning
confidence: 99%
“…It serves as an inevitable precursor to the development of type 2 diabetes mellitus (T2DM) and may also be a trigger for cardiovascular diseases (CVDs). Given that IR is a pivotal unifying factor in MetS, 8 the refined pathophysiological definition of MHO may primarily hinge on insulin sensitivity 9 . Despite the contentious clinical significance of MHO as a “diagnosis,” it offers a distinctive human model system for investigating the underlying mechanisms promoting weight gain and metabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…IR is one of the main pathological mechanisms of obesity and cardiometabolic diseases, which plays an important role in the development of cardiometabolic diseases [9] . Research clearly showed that IR is closely related to visceral adiposity and patients with IR are more likely to have microvascular complications and cardiometabolic diseases [3,9] .…”
Section: Introductionmentioning
confidence: 99%
“…IR is one of the main pathological mechanisms of obesity and cardiometabolic diseases, which plays an important role in the development of cardiometabolic diseases [9] . Research clearly showed that IR is closely related to visceral adiposity and patients with IR are more likely to have microvascular complications and cardiometabolic diseases [3,9] . Therefore, the aim of present study was to investigate the relationship between VSR and multi-organ IR, which could lay down the pathophysiological mechanisms for further revealing the relationship between VSR and cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%